Two refined creep calculation methods of two-way prestressed concrete - Pengfei Wu; Xinyu Xu; Zhichun Fang (PLoS ONE, 2025)
With the advancement of engineering technology, prestressed concrete has been increasingly applied in various structures. To accurately and efficiently evaluate the long-term performance of prestressed concrete members, this paper proposes trapezoidal and difference methods for long-term deformation calculation based on the principle of creep superposition. Compared with existing creep refinement approaches and experimental data, the methods presented in this study demonstrate higher accuracy. Moreover, they significantly reduce computational complexity, offering a practical theoretical foundation for creep analysis in large-scale structures. These methods are further extended to two-way prestressed concrete members, addressing the engineering need for accurate long-term performance evaluation in such systems. The findings indicate that the creep development in two-way prestressed members is slower than that in one-way members.